Ways of Developing Islamic Banking in the Process of Transforming our National Economy - Bayjanov Damir Sarsengalievich (International Journal on Integrated Education, 2022)
In this article, this article is about to develop the activities of Islamic banking, the history of the Islamic bankruptcy system, and the history of the Islamic bankruptcy system, as well as the history of the Islamic bankruptcy system, and the development of the Islamic bankruptcy and the prospects of the country will also be developed and the prospects of development. In particular, Uzbekistan provides existing problems in the development of the use of Islamic banking instruments and the author and proposals of the author to address them.